The phenotypic expression of mitochondrial tRNA-mutations can be modulated by either mitochondrial leucyl-tRNA synthetase or the C-terminal domain thereof - Giordano, Carla; Morea, Veronica; Perli, Elena; d’Amati, Giulia (Frontiers in Genetics, 2015)
Mutations in mitochondrial (mt) DNA determine important human diseases. The majority of the known pathogenic mutations are located in transfer RNA (tRNA) genes and are responsible for a wide range of currently untreatable disorders. Experimental evidence both in yeast and in human cells has shown that the detrimental effects of mt-tRNA point mutations can be attenuated by increasing the expression of the cognate mt-aminoacyl-tRNA synthetases (aaRSs). In addition, constitutive high levels of isoleucyl-tRNA syntethase have been shown to reduce the penetrance of a homoplasmic mutation in mt-tRNAIle in a small kindred. More recently, we showed that the isolated carboxy-terminal domain of human mt-leucyl tRNA synthetase (LeuRS-Cterm) localizes to mitochondria and ameliorates the energetic defect in transmitochondrial cybrids carrying mutations either in the cognate mt-tRNALeu(UUR) or in the non cognate mt-tRNAIle gene. Since the mt-LeuRS-Cterm does not possess catalytic activity, its rescuing ability is most likely mediated by a chaperon-like effect, consisting in the stabilization of the tRNA structure altered by the mutation. All together, these observations open potential therapeutic options for mt-tRNA mutations-associated disease